2020
DOI: 10.1007/s10462-020-09825-6
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the recent architectures of deep convolutional neural networks

Abstract: Deep Convolutional Neural Networks (CNNs) are a special type of Neural Networks, which have shown exemplary performance on several competitions related to Computer Vision and Image Processing. Interesting application areas of CNN include Image Classification and Segmentation, Object Detection, Video Processing, Natural Language Processing, Speech Recognition, etc. The powerful learning ability of deep CNN is largely due to the use of multiple feature extraction stages that can automatically learn representatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
975
0
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,030 publications
(1,197 citation statements)
references
References 209 publications
1
975
0
24
Order By: Relevance
“…There has been continuous evolution of CNN architectures in terms of increased depth (number of layers) for better performance but recent improvement in the representational capacity of deep CNNs has been attributed to the restructuring of processing units (e.g., having multiple paths and connections) rather than just increasing depth [26]. The better performance of MangoYOLO compared to deeper CNN architecture of YOLOv3 for panicle detection is consistent to the report of [12] for fruit detection, and can be ascribed to CNN design considerations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been continuous evolution of CNN architectures in terms of increased depth (number of layers) for better performance but recent improvement in the representational capacity of deep CNNs has been attributed to the restructuring of processing units (e.g., having multiple paths and connections) rather than just increasing depth [26]. The better performance of MangoYOLO compared to deeper CNN architecture of YOLOv3 for panicle detection is consistent to the report of [12] for fruit detection, and can be ascribed to CNN design considerations.…”
Section: Resultsmentioning
confidence: 99%
“…However, performance is also related to architecture (connecting layers, etc.) as well as depth [26]. A comparison of the R 2 CNN-upright method with its deeper CNN classifier (ResNet101) to the singleshot MangoYOLO(-upright) method is useful in this respect.…”
Section: Deep Learning Methods: a Comparisonmentioning
confidence: 99%
“…In contrast, the deep learning approach is based on transfer learning of open available CNNs trained on natural images, for example, GoogLeNet, Inception, ResNet, or, more optimal, a CNN trained for a similar purpose. Different deep CNN architectures were compared, for example, by Khan et al (2019) and Shin et al (2016). Spheroid's equatorial plane projections are reduced to three colours, for example, basolateral surface in green, nuclei in blue, and actin or apical surface in red/magenta, and converted to 8-bit RGB images.…”
Section: Outline Of Automated Analysismentioning
confidence: 99%
“…To overcome these shortcomings and enable fully automated LD recognition in QPI, we explored various supervised machine learning methods. Using Yarrowia lipolytica, (Figure 1), a tractable oleaginous yeast [54][55][56], we explored simple ensemble decision tree models, including random forest [57,58] and gradient boosting [59,60], as well as deep learning convolutional neural network (CNN) [61][62][63][64]. We found that CNNs outperform decision tree models in a number of metrics, including normalized template cross-correlation and the Sørensen-Dice coefficient (i.e., "Dice scores" [65][66][67][68]).…”
Section: Introductionmentioning
confidence: 99%